2019
DOI: 10.1002/nau.23915
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of adherence to urinary self‐catheterization in older adults

Abstract: Aims The primary aim is to explore the adherence predicting factors in clean intermittent self‐catheterization (CISC) in patients aged over 65 years. The secondary aim is to assess whether in this population, the non‐adherence risk is greater, compared with patients under 65. Methods All patients older than 65 that successfully learned CISC between January 2011 and January 2016 were included. A control population younger than 65 matched with sex, body mass index, and pathology was selected. Results One hundere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
10
2
2
Order By: Relevance
“…Some studies have been conducted to explore factors limiting CISC, whether difficulties in learning or in continued use. These studies found that obesity, being female, or having a motor or cognitive disorders have a negative impact on the ability to learn CISC, and older age, important stress urinary incontinence, and dependency for CISC installation were predictive for a poorer adherence to the method …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been conducted to explore factors limiting CISC, whether difficulties in learning or in continued use. These studies found that obesity, being female, or having a motor or cognitive disorders have a negative impact on the ability to learn CISC, and older age, important stress urinary incontinence, and dependency for CISC installation were predictive for a poorer adherence to the method …”
Section: Introductionmentioning
confidence: 99%
“…Two recent retrospective cohort studies investigating risk factors for failure to learn and adhere to CISC demonstrated that patients with obesity and a low Pencil and Paper test score (a 4-min test that includes exercises of grip, access to perineum, and cognitive tasks to explore the global capacity for the patient to self-catheterize) are less likely to be good candidates for CISC [105,106]. Age > 65 was not predictive of failure.…”
Section: Voiding Dysfunction and Retentionmentioning
confidence: 98%
“…We found 23 articles, of which 10 had data extracted [93][94][95][96][97][98][99][100][101][102]. Thirteen additional articles provided information pertinent to management of voiding dysfunction during this pandemic [103][104][105][106][107][108][109][110][111][112][113][114][115]. Based on review of the literature (23 articles) and expert consensus:…”
Section: Voiding Dysfunction and Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is vital that patients have good dexterity to enable precise positioning and insertion of the catheter to effectively perform CISC (Robinson, 2006). Above all, through dialogue, nurses must evaluate patient satisfaction, attitude and persistence of carrying out CISC, as these factors are known to influence adherence (Barbosa et al, 2012;Hentzen et al, 2019).…”
Section: Patient Assessment and Competency Of Ciscmentioning
confidence: 99%